The biomechanics of situational baseball: Execution and perception of left-handed pitchers' simulated pick-off moves to first base - Fortenbaugh, D.; Butcher-Mokha, M. (Sports Biomechanics, 2007)
The aim of this study was to provide an in-depth analysis of the pick-off play in baseball. Ten collegiate left-handed pitchers and nine base-runners participated in this study. The pitchers were videotaped with four cameras to derive three-dimensional data while performing deliveries in the directions of first base and home plate in a laboratory setting. Deliveries were performed from flat ground. Differences between these deliveries were measured through ten selected joint and segment angles. The base-runners completed two distinct procedures in which they viewed video footage of left-handed pitchers and estimated the intended delivery direction. Base-runners were subsequently interviewed to determine the reasoning behind their decisions. The pitchers' data revealed differences between delivery types in nearly all of the selected angles (P < 0.01). The base-runners' data demonstrated that their ability to discriminate delivery types improved when allowed more viewing time per trial (P < 0.01). Additionally, commonalities exist among the base-runners' focal points on the pitcher while making decisions regarding delivery direction and the kinematic differences between deliveries in left-handed pitchers. The practical significance of these results, however, may be more difficult to interpret.